Experimental Investigations on Erosion-Corrosion Characteristics of HVOF-Sprayed WC-10% Ni Coatings Deposited on Aluminum Alloy - G. S. Pradeep Kumar; Sampreeth Sunkad; R. Jogeshwar; R. Keshavamurthy; Vijay Tambrallimath; Sasidhar Jangam; Dadapeer Basheer (Advances in Materials Science and Engineering)
The current work investigates the erosion-corrosion behaviour of thermally sprayed tungsten carbide-10% nickel (WC-10% Ni) coatings placed on the AA6061 aluminum alloy. The AA6061 aluminum alloy was coated with tungsten carbide –10% nickel coatings utilising a high-velocityoxy-fuel (HVOF) spray method. The microstructure and hardness of thermally sprayed coatings were examined using a scanning electron microscope (SEM) and a Vickers hardness tester. The slurry erosion-corrosion wear tests were carried out by varying the parameters of the slurry erosion process, such as testing time, slurry content, slurry speed, and impinging particle size, on the erosion testing equipment. The data demonstrated that when slurry concentration, slurry speed, and impinging particle size increased, so did the slurry erosion-corrosion wear loss. The wear processes of uncoated and thermally sprayed tungsten carbide –10% nickel have been examined using SEM and a 3-D confocal microscope.